PRESEPSIN AS A POTENTIAL BIOMARKER OF SEPSIS IN PEDIATRIC PATIENTS UNDERGOING OPEN-HEART SURGERY - Julia Fitriany; Mulyadi M Djer; Novie Amelia Chozie; Piprim Basarah Yanuarso; Nina Dwi Putri; Irene Yuniar (International Archives of Medical Sciences and Public Health, 2026)
Sepsis after pediatric open-heart surgery is rare but highly lethal. Diagnosis is challenging because sepsis symptoms often overlap with post operative inflammatory responses. This study assessed presepsin as a biomarker for postoperative sepsis in children with congenital heart disease. In this prospective diagnostic accuracy study at Cipto Mangunkusumo National Central Hospital, Jakarta, 49 children undergoing open-heart surgery were enrolled. Plasma presepsin and procalcitonin (PCT) levels were measured on postoperative day 1 (T1) and day 3 (T3). Diagnostic performance was evaluated using ROC analysis. Presepsin levels were higher in septic than non-septic patients at T1 (415 vs. 141.5 pg/mL) and T3 (624 vs. 75.9 pg/mL), with a significant difference at T3 (p = 0.001). Presepsin was unrelated to surgical complexity but was associated with 7-day mortality (p = 0.013). At T3, presepsin showed better diagnostic accuracy than PCT (AUC 0.945 vs. 0.895). Optimal cutoffs were 404 pg/mL (T1) and 203.5 pg/mL (T3). PCT levels declined over time in septic patients. Presepsin is a promising biomarker for detecting postoperative sepsis in pediatric open-heart surgery patients, demonstrating diagnostic performance comparable to or superior to PCT, particularly on postoperative day 3. Serial monitoring may facilitate earlier identification of septic complications.